Aesthetic practices and politics in media, music, and art: performing migration - Davis, Rocío G.; Fischer-Hornung, Dorothea; Kardux, Johanna C. (Routledge, 2010)
Features the essays that focus on the connection between issues of migration and media. This title addresses how their interconnection has become part of our understanding of the world's global cities, and the paradigms through which we think about ethnicity and nation
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Theater; Musik; Migration; Ethnizität; Fernsehen; Film